Analyses of Socioeconomic Factors influencing on-farm Conservation of Remnant Forest Tree Species: Evidence from Ghana - Danquah, Jones Abrefa; ., Ari Pappinen (Journal of Economics and Behavioral Studies, 2013)
The contribution of remnant trees in traditional agro forestry systems in recent times has attracted significant attention from policy makers, stakeholders, and academicians due to their important role in conserving biodiversity within agricultural systems, reserves of genetic resources and provision of other important environmental services. The study seeks to determine socioeconomic factors influencing farmers’ decision to maintain remnant trees in agricultural landscape. Data was solicited from 220 households in three rural communities through structured interviews and on farm visitations. We employed Poison and Negative Binomial Regressions to determine factors influencing rural farm households’ decision to retain remnants forest tree species in agro ecosystem. The regression results indicated that the key factors strongly affecting farmers’ on-farm conservation decision to retain remnant forest trees in agricultural landscape were age, gender, years of schooling, religion, land tenure, farmers’ perceptions to current environmental problems, distance to farm land, erosion and the size of the landholdings. The study recommends that forest governance with focus on collaborative forest resource management and equitable distribution of benefits generated from extraction of forest resources should be given high impetus in policy formulation. The needs and concerns of forest fringe communities should feature paramount in this regard.